Prognostic significance of compliance with fractional flow reserve guidance on diverse vessel-related clinical outcomes - Zhang, Yang; Yang, Bangguo; Ye, Yicong; Zhao, Xiliang; Ding, Yaodong; Ye, Yi; Zhang, Liang; Tan, Dawei; Zhang, Gong; Duan, Xiaoyu; Li, Quan; Zeng, Yong (Frontiers in Cardiovascular Medicine, 2024)
Background In patients underwent fractional flow reserve (FFR) assessment, a noteworthy proportion of adverse events occur in vessels in which FFR has not been measured. However, the effect of these non-target vessel-related events on the evaluation of FFR-related benefits remains unknown. Methods and results In this retrospective study, vessels subjected to FFR measurement were grouped as FFR-based approach and non-compliance with FFR based on whether they received FFR-based treatment. Using inverse probability of treatment weighting (IPTW) to account for potential confounding, we investigated the association between compliance with FFR and 5-year target vessel failure (TVF) non-target vessel failure (NTVF) and vessel-oriented composite endpoints (VOCEs). Of the 1,119 vessels, 201 did not receive FFR-based treatment. After IPTW adjustment, a signiﬁcantly lower hazard of TVF was observed in the FFR-based approach group (HR: 0.56; 95% CI: 0.34–0.92). While, the intergroup difference in hazard of NTVF (HR: 1.02; 95% CI: 0.45–2.31) and VOCEs (HR: 0.69; 95% CI: 0.45–1.05) were nonsignificant. Conclusions In patients with CAD subjected to FFR, the FFR-based treatment yields a sustained clinical benefit in terms of the risks of target vessel-related events. The dilution of non-target vessel-related events renders the difference favoring the FFR-based approach nonsignificant.